Pengaruh Teknik Think Talk Write (TTW) Berbantuan Media Gambar Berseri terhadap Keterampilan Menulis Teks Prosedur Siswa Kelas VII MTsN 6 Kota Padang - Putri, Rezi Novita; Abdurahman, Abdurahman (Journal of Education Language and Innovation, 2023)
The Merdeka Curriculum has four elements of Indonesian language learning outcomes: listening, reading, speaking, and writing. At the Junior High School (SMP/MTs) education level for class VII Indonesian language subjects, one of the writing skills of writing procedural texts. This research concerns the influence of the think-talk-write (TTW) technique on students’ procedural text-writing skills, which are still relatively low. This research aims to determine the effect of applying the think talk write (TTW) on students' ability to write procedural texts. This type of research is quantitative with experimental methods. The population in this study was all students in class VII MTsN 6 Padang City for the 023/2024 academic year, totaling 352 students, represented by a sample of 32 students selected using a purposive sampling technique. The data for this research are scores from procedural text writing tests before and after using the think-talk write (TTW) technique. The result of this research shows that there is an influence of the use of think talk write (TTW) as evidenced by the increase in the average student calculation from 71.35 with the qualification More than Enough (Ldc) to 80.73 with the qualification Good (B).